Returned straw type over soil temperature dominates microbial hotspot dynamics and SOC sequestration - Ying Shen; Xuyi Zhu; Qian Yang; Chunli Wang; Zhen Liu; Geng Li; Yakov Kuzyakov; Tangyuan Ning (Soil and Tillage Research, 2026)

Controlling nitrosamine accumulation in dry fermented sausages using Lacticaseibacillus rhamnosus H7: The role of physicochemical drivers and precursor depletion - Ying Yue; Ning Zhao; Bingrui Guo; Jing Lv; Xin Nie; Sufang Zhang; Yingxi Chen; Beiwei Zhu; Shengjie Li; Xinping Lin (Food Microbiology, 2026)

Recharge sources and genesis of underground brines in the Mahai Basin, Qaidam Basin, China: insights from hydrochemistry and multi-isotope tracers - Ruibo Liu; Xiwei Qin; Wenquan Lu; Haiyan Shi; Zhen Shi; Chenglin Liu; Ying Ma; Xiangjun Li; Sha Yang; Ziwen Jiang; Genhou Wang; Ming Ma; et al. (Carbonates and Evaporites, 2026)

Adaptive fault-tolerant control of gas-cooled microreactor based on model reference adaptive control - Wenqiang Li; Mingyue Jiang; Yongjian Ma; Shengyong Liao; Wenqing Yao; Ying Li; Ke Ning; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2026)

Decoding glomalin: Mycorrhizal hyphae-secreted glomalin-related soil protein in a zero-carbon background unveils Hsp60 homology and functional molecular architecture - Xiao-Qing Liu; Ci Deng; Li-Jun Zhou; Ying-Ning Zou; Qiang-Sheng Wu (Soil Biology and Biochemistry, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

Dynamic evolution mechanism of carbon oxides during Low-Temperature oxidation and an Early-Warning model for the spontaneous combustion risk of lignite - Zhenshuai Sun; Ning Li; Xianliang Meng; Fan Wu; Ruizhi Chu; Jianqiao Zhao; Shuo Li; Ying Feng; Hengbo Hu; Yihao Sun; Shi Yu (Fuel, 2026)

Fat reduction in emulsified pork sausages: role of pea protein-stabilized high-internal-phase emulsions - Chaoyue Yang; Beibei Li; Lihua Shang; Cinan Li; Yuqian Guan; Ying Chen; Ning Liu; Ying Zhou; Qiujin Zhu (Food Research International, 2026)

Perchlorate exposure in Chinese primary children: Levels, potential health risks, and association with sexual development - Yang Xiang; Cui-Lan Bai; Ting-Ting Xu; Yu-Ling Luan; Liang-Ying Liu; Li-Ning Zhao; Ying Guo (Environmental Pollution, 2026)

Spatiotemporally resolved LIBS for organic carbon quantification in shale: Decoupling inorganic carbon interference via plasma dynamics analysis - Minxin Chen; Jian Wu; Ying Zhou; Xinyu Guo; Ning Wang; Yiguo Chen; Xingwen Li; Aici Qiu (Analytica Chimica Acta, 2026)

Dynamic competitive constraint handling for constrained multi-objective optimization - Wei Li; Haoying Li; Ning Yang; Shuling Yang; Ying Huang (Swarm and Evolutionary Computation, 2026)

The role of different ionic celluloses in modulating myofibrillar protein gelation through high internal phase Pickering emulsions - Cinan Li; Yang Wang; Chaoyue Yang; Lihua Shang; Yuqian Guan; Ning Liu; Ying Chen; Yuanyuan Liu; Qiujin Zhu; Ying Zhou (Meat Science, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Rapid formation of partial denitrification granular sludge under an alkaline-assisted stepwise SBR strategy: XDLVO insights into interfacial adhesion and calcium-associated reinforcement - Dingying Ning; Wenqing Tian; Fuxiong Nan; Mingyue Li; Wenshuo Yang; Jie Lei; Jianjiang Ying; Jidong Liang (Chemical Engineering Journal, 2026)

Charge-programmable carbon dots tailored by amino acid pKa spectrum for spatiotemporally controlled siRNA delivery and antiviral protection in plants - Fang Wang; Xueyang Ji; Yan Zhao; Jingyan Hu; Ziqi Zhang; Jinxuan Wang; Kailin Su; Jingyan Jia; Ao Zhou; Ning Li; Ying Song; Changjun Zhang; et al. (Chemical Engineering Journal, 2026)

Impact of intraguild predation between Neoseiulus barkeri and Lasioseius scapulatus on thrips control in cowpea - Yuanming Chi; Chen Yu; Yilin Zhu; Kai Shu; Ying Gong; Huiyin Yang; Ning Nong; Zihan Zhao; Mingyue Feng; Maoqing Li; Yanyu Chen; Xinzheng Huang; et al. (Journal of Pest Science, 2026)

Information flow reveals three-tiered oceanic drivers of precipitation over the middle–lower Yangtze River Basin - Li-Ying Ning; Dan Wu; Ying Qu; Guo-Lin Feng; Yong-Ping Wu (Climate Dynamics, 2026)

Integrating agricultural management and factor interaction effects for interpretable maize yield prediction in the U.S. Corn Belt - Liang Li; Ning Lu; Mengmeng Hong; Ying Sun; Jiaxu Wang; Jun Qin (Agricultural and Forest Meteorology, 2026)

Mediation effects of thyroid hormones in the associations between essential metal elements and anxiety or depression symptoms in the elderly - Juanhua Li; Wenqi Wang; Yang Peng; Ning Qin; Jiemei Li; Ying Wei; Biwen Wang; Huaicai Zeng; Han Li; Lu Cheng (BioMetals, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Hydrate extraction riser gas-liquid-solid three-phase coupled flow simulation experiment: flow characteristics and prediction of flow pattern transition boundaries - Xiaoqiang Guo; Qi Gao; Yuechao Liu; Guanlong Jia; Ying Li; Jun Liu; Liming Dai; Ning Zong (Ocean Engineering, 2026)

Local polarization-piezoelectric field promotes water dissociation for efficient fluorinated pollutants defluorination - Yi Liu; Zhikui Zhou; Yuhang Xu; Xinyu Liu; Ying Zhou; Zixiang Lin; Ning Li; Li Yang; Xiaoyun Fan (Journal of Hazardous Materials, 2026)

Microclimate-adjusted carbon density modeling improves carbon density estimation for photovoltaic-impacted grasslands in Inner Mongolia - Jiaxu Wang; Ning Lu; Ying Sun; Liang Li; Jun Qin (Journal of Environmental Management, 2026)

Tris(2,4-di-tert-butylphenyl) phosphate promotes malignant phenotypes by triggering epithelial-mesenchymal transition in human bronchial epithelial cells: Implication from the mitochondrial localization of TDP-43 - Xiaofei Wang; Chengxu Zhang; Linfeng Zhu; Yinghao Chen; Ying Wang; Ru Chen; Dan Li; Jinsong Xue; Ning Zhang; Chunmei Ge (Journal of Environmental Sciences, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

In situ nanoencapsulation of curcumin in egg yolk low-density lipoprotein gels: Calcium-regulated protein network restructuring and stability enhancement - Jian Li; Qingruo Zhao; Xian Fang; Peiyao Si; Huajiang Zhang; Lina Xu; Ying Ma; Ning Xia; Hanyu Li; Mohamed Ghamry; Ahmed M. Rayan (Food Chemistry, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

Q estimation based on multi-trace and corresponding travel time spectral ratio method - Zhiwei Li; Ying Shi; Ning Wang; Siyuan Chen (Acta Geophysica, 2026)

A new flavonol glycoside isolated from the stems and leaves of Astragalus membranaceus - Jia-Xin Zhao; Yun Zang; Pei Li; Jia-Ning Zhang; Si-Qi Yang; Hui-Feng Li; Yan Wang; Jin-Yan Tan; Ying-Li Wang; Yan-Gang Cheng (Natural Product Research, 2026)

Expression of Transforming Growth Factor Beta 1 in Lung Adenocarcinoma and Its Relationship with Circulating Tumour Cells - Ning Chen; Duo-Jun Qiu; Jian-Zhu Yang; Gui-Yun Zhu; Li-Fei Kang; Xiao-Ying An; Zhi-Ming Xu; Xiao-Xia Li (Biochemical Genetics, 2026)

The vertical distribution and redox-dependent mobilization of arsenic in naturally contaminated karstic paddy soils from southwestern China - Qi Gao; Manman Zhao; Ying Wang; Hang Li; Zengping Ning; Jing Sun; Chengshuai Liu; Yizhang Liu (Applied Geochemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Antibacterial mechanism of octyl gallate against methicillin-resistant staphylococcus aureus and its application in pork preservation: insights from multi-omics and computational simulation - Saiqing Xu; Huan Li; Ying Xie; Ke Ding; Ning jiang; Rongrong Wang; Shenghua Ding (Food Research International, 2026)

EGCG combined with pulsed ultrasound inhibited browning of frozen-thawed apples by synergistically stabilizing cell structures, inducing flavonoid accumulation, and inhibiting PPO expression - Haiying Yang; Yawen Li; Jiani Chen; Zijun Wang; Ying Xie; Saiqing Xu; Jia Guo; Rongrong Wang; Ning Jiang; Yang Shan; Shenghua Ding (Food Chemistry, 2026)

ZNRF2-mediated CD-M6PR degradation and lysosomal dysfunction aggravate cellular senescence and aging - Tingting Zhao; Weitong Xu; Fangfang Wang; Honghan Chen; Hui Gong; Yu Yang; Ning Huang; Ming Yang; Jian Zhang; Chuhui Gong; Xiaoli Huang; Ying Li; et al. (GeroScience, 2026)

Three phloridzin derivatives capable of anti-oxidant from Malus toringoides (Rehd) Hughes - Li Liu; Wei-wei Tian; Ying-chao Wang; Can Ren; Dong-mei Yu; Jian-bo Wang; Jun-ning Zhao; Hua Hua (Natural Product Research, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Substrate control and carrier bioaugmentation stabilize the electrocatalytic-Anammox process for sustainable nitrogen removal - Kaiqiang Liang; Ying Liu; Xiaojuan Wu; Heyi Wang; Jian Li; Xinlin Li; Wei Yan; Jiangtao Feng; Ning Wang (Journal of Water Process Engineering, 2026)

Dose and food matrix effects on selenium retention in mouse tissues from selenium-rich vegetables and rice: Implications for selenium bioavailability - Jin-Feng Xi; Xin-Ying Lin; Ning Wang; Jin-Lei Yang; Dongmei Zhou; Hong-Bo Li (Journal of Trace Elements in Medicine and Biology, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Toward a comprehensive map of Rab-mediated cargo transport to migrasomes - Yiling Wen; Yong Li; Jiayi Chen; Dianxing Liu; Yuanchao Li; Ying Li; Haohao Tang; Peizhen Gao; Wenmin Tian; Ning Shen; Yang Chen (Science China Life Sciences, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Artemisia argyi essential oil - loaded β-cyclodextrin/whey protein microcapsules: dual antifungal and disease resistance-inducing effects to enhance blueberry shelf life - Yue-yan Chen; Ning-ying Zhu; Wei Gao; Yu Wang; Mei-qing Li; Dong-liang Wang; Xue-ling Gao; Jin Liang; Hai-wei Zhang (Food Chemistry, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

Conservation mulching with plastic film in maize field of arid irrigation region: Agronomic performance, economic, and environmental effects - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Xiao-Yu Lu; Ying Zhu; Meng Hao; Ning Wang; Meng-Ying Li; Xiao-Feng Zhang; Hong-Yan Tao; You-Cai Xiong (Field Crops Research, 2026)

Advanced composting simulation technologies: A systematic review of methodological frameworks and applications - Ming-xiao Li; Ning Wang; Yuan-yuan Xie; Mei-ying Ye; Bei-dou Xi; Wang-mi Chen; Qi Zhou; Jian-long Hu; Jia-qi Hou (Journal of Environmental Management, 2026)

Cadmium solubility in alkaline paddy soils with contrasting Cd sources and biogeochemical properties under redox alternation - Yizhang Liu; Ying Wang; Yongxiang Zhang; Yuyang Li; Enzong Xiao; Zengping Ning; Jing Sun; Chengshuai Liu (Journal of Environmental Sciences, 2026)

Breaking the HCl/SO2 selectivity barrier: Intrinsic basic properties of MDEA/SBA-15 for HCl removal - Xingguang Hao; Ying Zhu; Lei Shi; Fei Wang; Xin Sun; Ping Ning; Kai Li (Fuel, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Beyond astaxanthin: The bioactive ingredients of Haematococcus pluvialis and their applications in food - Shu-tao Sun; Yan-jie Jiang; Jesus Simal-Gandara; Xu Guo; Shengxiang Yang; Ying-ying Chen; Meng-qi Zhang; Qi-dong Ren; Mu-xuan Wang; Jin-yue Sun; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2026)

Devonian brachiopod palaeobiogeography in the Qamdo Block, Eastern Tibet, China - Li Qiao; Wen-Kun Qie; Wen Guo; Cong-Ying Liu; Jin-Ning Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Substrate-driven microbial diversity and functional potential of plastisphere biofilms in a dynamic coastal ecosystem of northeastern Taiwan - Priyanka Muthu; Sakcham Bairoliya; Gowri Krishna Girija; Li-Chun Tseng; Bin Cao; Jiang-Shiou Hwang; Ying-Ning Ho (Environmental Pollution, 2026)

Comparative study on nitrogen removal through partial denitrification coupled with Anammox by using biofilter and continuous stirred tank reactor - Longyan Chang; Dingying Ning; Fuxiong Nan; Wenshuo Yang; Yile Fan; Wenqing Tian; Mingyue Li; Jianjiang Ying; Di Wu; Jidong Liang; Wei Yan (Bioresource Technology, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Patterns of rhizosphere microbial community assembly affect blueberry growth: environmental and host effects - Chunhuan Li; Ning Jiao; Siyu Liu; Laiye Qu; Ying Zhang; Naili Zhang (Rhizosphere, 2025)

Toward structured and functional salted egg yolks: Role of calcium chloride concentration on protein conformation, aggregation, and gel formation under sodium chloride dry-curing - Jian Li; Rui Chuang; Jiayu Liang; Huajiang Zhang; Lina Xu; Ying Ma; Ning Xia; Yonggang Tu; Ahmed M. Rayan; Mohamed Ghamry (Food Research International, 2025)

Anion/cation co-etching of ZIF-67 to derive hollow-structured high-efficiency seawater electrocatalysts for resisting chloride corrosion - Shunli Li; Zhiyu Hu; Yan Zheng; Tianbo Jia; Xiang Li; Ying Wang; Qitao Wu; Xueya Zhu; Lizhen Su; Ning Yu; Yingtang Zhou; Jinshu Lu; et al. (Chemical Engineering Journal, 2025)

First pathogenic non-coding variant in MMACHC: a functional deletion in the 5′-UTR associated with cobalamin C deficiency - Ying Zhang; Leyi Wang; Xiangyu Liu; Mei Sun; Hong Wang; Jiaci Li; Shuyue Zhang; Ning Zhang; Dong Li; Jianbo Shu; Chunquan Cai (Molecular Biology Reports, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Transcriptome analysis of the hypothalamus and testes in Brandt’s Vole: new insights into mechanisms of photoperiodic plasticity in postnatal testicular development - Lewen Wang; Yaqi Ying; Ning Li; Ying Song; Lijuan Zhao; Hong Sun; Zhenlong Wang; Xiao-Hui Liu; Dawei Wang (Functional & Integrative Genomics, 2025)

Water quality monitoring optimization based on human activity intensity: a case study of the Ganjiang River Basin - Yuan Ying; Bao Ning; Li Lanhui; Deng Fuliang; Li Hui (Environmental Monitoring and Assessment, 2025)

Short-term no-tillage improves soil water retention and maintains soil aeration at high moisture conditions despite reduced macroporosity - Jing Tan; Bingcheng Si; Ying Zhao; Yili Lu; Yuxin Chen; Ning An; Song Li; Weichao Wang; Han Fu; Wei Han; Yanli Yi (Soil and Tillage Research, 2025)

Achieving partial nitritation-anammox in membrane-aerated biofilm reactor by hydroxylamine addition - Ning Mei; Fangxu Jia; Ying Liu; Yiran Li; Xin Qi; Baohong Han; Xu Zhang; Tao Liu; Hong Yao (Journal of Environmental Management, 2025)

Spatio-temporal prevalence and distribution of Salmonella spp. serovars in animal-origin foods in China: A comprehensive outlook derived from nine years of national surveillance, 2014—2022 - Ying Li; Lisha Liu; Li Bai; Zhaoping Liu; Ning Li; Weijun Kang; Dajin Yang; Zixin Peng; Lingmei Niu (Food Research International, 2025)

Safety and recyclability of active polyethylene terephthalate bottles: A comprehensive assessment using non-target screening and visual sensory evaluation - Can Xu; Sheng Chen; Qi-zhi Su; Jinxin Liang; Ying Zeng; Anqi Cui; Hanke Li; Ben Dong; Dan Li; Huai-ning Zhong (Food Chemistry, 2025)

Reinforcement knowledge sharing assisted two-archive evolutionary algorithm for many-objective optimization - Qing Xu; Shuzheng Xie; Ning Yang; Ying Huang; Shaochang Nie; Wei Li (Swarm and Evolutionary Computation, 2025)

Effect of oleic acid iodine value on the flotation performance of oleic acid-based collectors for spodumene - Ying Zhang; Ning Sun; Yuhua Wang; Liu Luo; Man Cui; Yu Li (Journal of Environmental Chemical Engineering, 2025)

Unveiling Moxibustion's Impact on AD Mice Learning and Memory: Role of Mitochondrial Respiratory Chain Complex I Subunit in the Hippocampus - Yuan Shen; Hong-Ying Li; Qing-Qing Yang; Ke Zhang; Shu-Qing Liu; Ning Zhang; Chen-Yu Li; Shu-Guang Yu; Lu-Shuang Xie; Qiao-Feng Wu (Molecular Neurobiology, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

Multi-omics profiling reveals infectious bursal disease virus-induced alterations in gene expression and metabolism in chicken bursa of fabricius - Cuiping Song; Siyu Li; Yanmei Yuan; Wei Gao; Xusheng Qiu; Lei Tan; Yingjie Sun; Ning Tang; Yang Qu; Ying Liao; Chan Ding (Veterinary Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficient phosphate removal from wastewater using Mg/Fe-functionalized tea stalk biochar through green synthesis and bio-assembly method - Huiyao Li; Shuai Shi; lrina lvshina; Ziyan Wang; Jing Gui; Ruolai Wang; Chunyu Pan; Yiwen Ning; Jianhua Qu; Siyue Han; Ying Zhang (Process Safety and Environmental Protection, 2025)

Impact of cationic reagent structure on the performance of combined collectors in spodumene-feldspar flotation system - Ying Zhang; Yuhua Wang; Ning Sun; Haiqiang Feng; Yu Li; Man Cui (Minerals Engineering, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Volatilomics and Lipidomics revealed flavoring mechanism in baijiu brewed from diverse Sorghum varieties - Hui Zhu; Linjuan Li; Yi Ma; Huibo Luo; Ahmed H. El-Sappah; Ying Liu; Xiaoke Sun; Shijiang Pan; Muhammad Aamer Mehmood; Yong Sun; Ning Wang (Food Chemistry, 2025)

A Seismic Multi-Attribute Sandbody Identification Method Based on the LightGBM-RFECV Coupling Algorithm - Teng-fei Ren; Zhi-bing Feng; Ying Zhang; Xiang Zhang; Li Jiang; Yuan-li Ning; Jing-yi Wang; Jian Ding; Zeng-shuo Qi (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

New Insights Into the Phylogeny and Biogeography of Goji Berries ( Lycium , Solanaceae) Inferred From Plastid Data - Gulbar Yisilam; Kenneth M. Cameron; Zhi‐Yong Zhang; En‐Ting Zheng; Chuan‐Ning Li; Zhen‐Zhou Chu; Ying Su; Jia‐Lei Li; Yu‐Wei Wang; Jin Li; Pan Li; Xin‐Min Tian (Journal of Biogeography, 2025)
Aim Lycium L. (Solanaceae), which is known for producing goji berries, is an important plant with both medicinal and edible uses. This genus is globally distributed in temperate and subtropical regions. However, a comprehensive phylogeny and evolutionary history of this plant group is lacking so far. This study was executed to produce novel insights into the phylogenetic relationships and evolutionary history of this small but economically important genus. Location North America, South America, Hawaii, Africa and Eurasia. Taxon Lycium L. (Solanaceae). Methods We established a phylogenetic framework for Lycium based on complete plastome sequences and data from 80 protein‐coding genes across 43 Lycium species using maximum likelihood and Bayesian inference methods. Furthermore, 14 species from the Solanaceae family were used as outgroups. Additionally, two Solanoideae fossils and one secondary calibration point were used to estimate divergence times and reveal the biographical history of these plants through ancestral area reconstruction. Results Our analysis revealed that six North American Lycium species were strongly supported as monophyletic with high support and were sister clades to the remainder of the genus. The remaining species from North America, South America and the Hawaiian Islands shared a common ancestor, whereas all species from Africa, Saharo‐Arabia and Eurasia formed a distinct clade. Our results indicated that Lycium originated in North America during the Late Oligocene and then dispersed to Hawaii and South America, from there to Africa, and then further to Saharo‐Arabia, with a more recent dispersal to Eurasia. Main Conclusions Our plastid genome data confirmed that Lycium originated in North America and identified long‐distance dispersal as the key to its global distribution. Genomic insights facilitate species identification and contribute to conservation efforts.

Warming exacerbates the effects of pesticides on the soil collembolan gut microbiome and antibiotic resistome - Ya-Ning Wang; Tian-Gui Cai; Ying Li; Wen-Cai Dai; Da Lin; Jin-Ting Zheng; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2025)

Comprehensive analysis of the effect of Staphylococcus xylosus YCC3 fermentation on bacterial community, flavor and lipid metabolism of fermented sausages - Yingying Dong; Ying Liu; Ning He; Xiaodong Li; Yingchun Zhu (Food Bioscience, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

How indoor decoration materials contribute to phthalates pollution: Uncovering occurrences, sources, and their implications for environmental burdens in households - Hao-Yang Shen; Ying Zhang; Xin-Yu Lu; Li-Bo Chen; Ning-Zheng Zhu; Hang Xiao; Guojing Yang; Cenyan Huang; Xiaorong Dai; Jien Ye; Dezhen Chen; Hui Li; et al. (Journal of Hazardous Materials, 2025)

A highly stable zinc phosphonate for efficient heterogeneous catalytic CO2 cycloaddition and ring-opening reaction - Chao-Ying Gao; Yakun Wu; Ling Ding; Yang Li; Wenbo Wang; Ning Xu; Jinghai Liu; Yang Yang (Journal of Environmental Chemical Engineering, 2025)

Eriocheir sinensis CD63 activate mitochondria-mediated apoptosis to resist Spiroplasma eriocheiris infection - Wenbo Li; Guanzheng Yang; Yangzhi Fan; Xinru Yan; Zhuoqing Li; Ying Guo; Qing Wang; Xuguang Li; Wei Gu; Mingxiao Ning; Jun Zhou; Qingguo Meng (Fish & Shellfish Immunology, 2025)

Gas permeability and microscopic mechanisms of Xanthan gum-amended compacted lean clay as a gas barrier material - Ying-Zhen Li; Jia-Lei Wan; Fei Jin; Krishna R. Reddy; Ning-Jun Jiang; Yan-Jun Du (Engineering Geology, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

Therapeutic Hypothermia and Recombinant Erythropoietin Mitigate Brain Microvascular Endothelial Cell Dysfunction via Modulating the Pentose Phosphate Pathway - Jinan Han; Ying Xu; Yan Zhou; Ning Zhu; Jiazhen Gao; Li Huang (Journal of Molecular Neuroscience, 2025)

Proteome profiling of the lung tissues of the mice co-infected with H9N2 influenza A virus and Pseudomonas aeruginosa - Sun Ying-Li; Fan Hua; Li Wen-qian; Li Dan; Bai Ke-fei; Dong Lu-jiao; Zhang Hui-ning; Li Jian-liang; Xie Zhi-jing (Veterinary Microbiology, 2025)

Influence of two sorghum varieties on metabolic factors, microbial community, and flavor component precursors of strong-flavor Baijiu Zaopei - Hui Zhu; Qiang Li; Ahmed H. El-Sappah; Yong Sun; Ying Liu; Shijiang Pan; Ke Zhu; Xiaoke Sun; Tao Xiong; Huibo Luo; Tao Wu; Linjuan Li; et al. (Food Chemistry, 2025)

Prospecting artificial microbial consortia toward lignin valorization - Jian-Ning Hu; Bo-Chao Gao; Zhi-Hua Liu; Xia Li; Ying-Jin Yuan; Bing-Zhi Li (Chemical Engineering Journal, 2025)

Dynamic covalent synthesis of highly-crystalline and fully-cyclized aromatic COF as an artificial interphase layer toward stable lithium metal batteries - Wei Shao; Da Xu; Tiantian Wang; Huanghao Pan; Ying Liu; Xue Gao; Jiahuan Luo; Jing Wang; Zhong-Kun Li; Yao Guo; Huihui Zhao; Ning Fu; et al. (Chemical Engineering Journal, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Ginkgoites manchurica from the Lower Cretaceous Shahezi Formation of Liaoning, China, and its palaeoclimate implications - Yan Liu; Qiao-Er Ying; Qi-Jia Li; Ning Zhou; Chao Zhang; Yu-Jin Zhang; Xiao Tan; Fei Liang (Palaeoworld, 2025)

Etiological characterization of multiple recombinant lineages of TJ-C6 porcine reproductive and respiratory syndrome virus in Tianjin, Northern China - Yong Li; Cheng Yang; Xin-lei Li; Jiu-ying Sun; Ning Cheng; Kai-yue Wang; Ying-Feng Sun (Veterinary Research Communications, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

The aging and pollution behavior of microplastics in tap water supply system subjected to residual chlorine exposure - Pengxiao Liu; Shuai Gao; Ying Li; Bin Hou; Ning Liu; Zhen Du; Jing Lu (Environmental Science and Pollution Research, 2025)

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Exposure to oxygenated polycyclic aromatic hydrocarbons and endocrine dysfunction: Multi-level study based on hormone receptor responses - Ying Ren; Yue Wang; Yang Wang; Xia Ning; Guangke Li; Nan Sang (Journal of Hazardous Materials, 2025)

Microbial community structure and water quality performance in local scrubber reclaim system for water reclamation of the semiconductor industry: A case study of a semiconductor plant in Beijing - Yu-Di Li; Yin-Hu Wu; Hao-Bin Wang; Rui-Ning Wang; Pei-Hua Li; Bang-Hao Huang; Hong-Ying Hu (Environmental Research, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

The effect of heatwave and cold spell on cardiovascular disease mortality in central China, 2018–2022 - Ling-Shuang Lv; Li Yin; Yuan Liu; Chun-Liang Zhou; Ji Hu; Ning An; Xian Xie; Xing-E Zhang; Min Zhang; Xiu-Ying Liu (International Journal of Biometeorology, 2025)

Roles of straw return in shaping denitrifying bacteria in rice rhizosphere soils through effects on root exudates and soil metabolites - Pei Chen; Yu Cheng; Ning Wang; Jian-Guang Yu; Ying Zhao; Li-Hong Xue (Soil Ecology Letters, 2025)

Stem cells vesicles-loaded type I pro-photosensitizer for synergetic oxygen-independent phototheranostics and microenvironment regulation in infected diabetic wounds - Qin Zeng; Ying Zhang; Judun Zheng; Jingyan Lin; Ning Li; Minghai Zhao; Xu Chen; Xipeng Li; Meijiao Zhao; Jialin Huang; Qiulin Xie; Ronghua Yang; et al. (Chemical Engineering Journal, 2025)

Spatiotemporal Mapping of the Oxytocin Receptor at Single-Cell Resolution in the Postnatally Developing Mouse Brain - Hao Li; Ying Li; Ting Wang; Shen Li; Heli Liu; Shuyi Ning; Wei Shen; Zhe Zhao; Haitao Wu (Neuroscience Bulletin, 2025)
The oxytocin receptor (OXTR) has garnered increasing attention for its role in regulating both mature behaviors and brain development. It has been established that OXTR mediates a range of effects that are region-specific or period-specific. However, the current studies of OXTR expression patterns in mice only provide limited help due to limitations in resolution. Therefore, our objective was to generate a comprehensive, high-resolution spatiotemporal expression map of Oxtr mRNA across the entire developing mouse brain. We applied RNAscope in situ hybridization to investigate the spatiotemporal expression pattern of Oxtr in the brains of male mice at six distinct postnatal developmental stages (P7, P14, P21, P28, P42, P56). We provide detailed descriptions of Oxtr expression patterns in key brain regions, including the cortex, basal forebrain, hippocampus, and amygdaloid complex, with a focus on the precise localization of Oxtr + cells and the variance of expression between different neurons. Furthermore, we identified some neuronal populations with high Oxtr expression levels that have been little studied, including glutamatergic neurons in the ventral dentate gyrus, Vgat + Oxtr + cells in the basal forebrain, and GABAergic neurons in layers 4/5 of the cortex. Our study provides a novel perspective for understanding the distribution of Oxtr and encourages further investigations into its functions.

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Preparation and characterization of a novel green cinnamon essential oil nanoemulsion for the enhancement of safety and shelf-life of strawberries - Yue Zhu; Teng Chen; Zejing Meng; Tingyu Li; Jiaojiao Zhang; Ning Zhang; Gang Luo; Zuhua Wang; Ying Zhou (International Journal of Food Microbiology, 2025)

On-demand removable hydrogel film derived from gallic acid-phycocyanin and polyvinyl alcohol for fruit preservation - Wei Gong; Ting-qi Yang; Wan-ying He; Yu-xin Li; Jiang-ning Hu (Food Chemistry, 2025)

Selection of signature peptide biomarkers for the sesame allergens in commercial food based on LC-MS/MS - Jing Li; Wenhan Kang; Jiukai Zhang; Yiqiang Ge; Ning Yu; Ying Chen (Food Chemistry, 2025)

Mesoporous dual-atom nanozyme induced cuproptosis and apoptosis for boosting immunogenic cell death along with reprogramming tumor immune-suppressive microenvironment - Yunhao Wang; Lei Ding; Ziguo Lin; Baolong Li; Di Hu; Shichen Zhang; Shujun Zhou; Yuxiang Ning; Fei Xin; Yunfei Ying; Fukai Zhu; Peiyuan Wang; et al. (Chemical Engineering Journal, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

Detection of organic carbon in shale by laser induced breakdown spectroscopy and Raman spectroscopy combined with partial least squares methods - Di Wu; Jian Wu; Mingxin Shi; Ning Wang; Yiguo Chen; Xinyu Guo; Ying Zhou; Xingwen Li; Aici Qiu (Analytica Chimica Acta, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Research advances in citrus polyphenols: green extraction technologies, gut homeostasis regulation, and nano-targeted delivery system application - Yahui Liu; Ning Yan; Qin Chen; Lezhen Dong; Ying Li; Peifang Weng; Zufang Wu; Daodong Pan; Lingyi Liu; Mohamed A. Farag; Lei Wang; Lianliang Liu (Critical Reviews in Food Science and Nutrition, 2024)

Microbiome flexibility enhances the resilience of the potentially invasive coral Tubastraea aurea to abrupt environmental changes: Insights from a shallow water hydrothermal vent transplantation study - Gowri Krishna Girija; Li-Chun Tseng; Priyanka Muthu; Yu-Ling Chen; Ying-Ning Ho; Jiang-Shiou Hwang (Science of The Total Environment, 2024)

Vkorc1 polymorphisms of the Norway rats in China: Implications for rodent management and evolutionary origin of anticoagulant resistance mutations - Xiuhui Wang; Xiaohui Ma; Meng Qin; Ting Sun; Dawei Wang; Ning Li; Xiaohui Liu; Meidong Jing; Deng Wang; Ying Song (Science of The Total Environment, 2024)

Biotransformation of enrofloxacin-copper combined pollutant in aqueous environments by fungus Cladosporium cladosporioides (CGMCC 40504) - Ning Ma; Hongyu Zhang; Lilai Yuan; Yingren Li; Wenbo Yang; Ying Huang (World Journal of Microbiology and Biotechnology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Genome-Wide Identification, Characterization, and Expression Analyses of the Mucin Genes in Japanese Flounder (Paralichthys olivaceus) - Ying Zhu; Xinsheng Yang; Xu Yan; Ning Yang; Min Cao; Chengbin Gao; Chao Li (Journal of Ocean University of China, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Bioconversion of lignans in flaxseed cake by fermented tofu microbiota and isolation of Enterococcus faecium strain ZB26 responsible for converting secoisolariciresinol diglucoside to enterodiol - JiaQi Zhu; Zizhe Cai; Ziliang Song; Ying Li; Youn Young Shim; Martin J.T. Reaney; Yee Ying Lee; Yong Wang; Ning Zhang (Food Chemistry, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Ozone-Induced Lung Injury are Mediated Via PPAR-Mediated Ferroptosis in Mice - Juan Li; Huai Wei; Ning Wang; Jing Chen; Ying Zhang; Zhen An; Jie Song; Tianqi Niu; Weidong Wu (Biological Trace Element Research, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Deciphering the triclosan degradation mechanism in Sphingomonas sp. strain YL-JM2C: Implications for wastewater treatment and marine resources - Piaopiao Pan; Yichao Gu; Tao Li; Ning-Yi Zhou; Ying Xu (Journal of Hazardous Materials, 2024)

In situ self-assembled CoS-Co9S8-NC homologous heterostructure on 3D interconnected carbon networks as a multifunctional separator for the high-rate and long-life Li-S batteries - Ying Zhang; Xuetao Shen; Hang Niu; Zhanxuan Zhou; Baorui Zhu; Liang Li; Ning Gao (Chemical Engineering Journal, 2024)

Urban heat island characteristics of Yangtze river delta in a heatwave month of 2017 - Ying Gao; Ning Zhang; Yan Chen; Ling Luo; Xiangyu Ao; Wenjuan Li (Meteorology and Atmospheric Physics, 2024)

Integrated systematic functional screen and fine-mapping decipher the role and genetic regulation of RPS19 in colorectal cancer development - Can Chen; Wenzhuo Wang; Caibo Ning; Zequn Lu; Ming Zhang; Ying Zhu; Jianbo Tian; Haijie Li; Yue Ge; Beifang Yang; Xiaoping Miao (Archives of Toxicology, 2024)

Enhanced waste water purification performance of solar-driven interfacial water evaporation through the integration of electrocatalysis - Chaorui Xue; Chi Zhang; Yu Zhang; Lei Liu; Wenjing Zheng; Ying Li; Huinian Zhang; Suping Jia; Ning Li; Qing Chang; Shengliang Hu (Journal of Water Process Engineering, 2024)

Indirect photodegradation of typical pyrrolizidine alkaloids in water induced by triplet states of dissolved organic matter - Menghong Gao; Shuili Yu; Rongsheng Ning; Xingli Ji; Ying Xu; Li’an Hou (Journal of Hazardous Materials, 2024)

Discover the secrets of salty taste in Manila clam (Ruditapes philippinarum): MALDI-TOF MS and flavor fingerprint - Chaonan Sun; Wenhui Zhu; Ying Bu; Yue Ning; Jianrong Li; Xuepeng Li (International Journal of Gastronomy and Food Science, 2024)

Screening of specific binding peptide for β-lactoglobulin using phage display technology - Ning Yu; Yan Yang; Yang Li; Wenhan Kang; Jiukai Zhang; Ying Chen (Food Chemistry, 2024)

Integrating RTM-GWAS and meta‑QTL data revealed genomic regions and candidate genes associated with the first fruit branch node and its height in upland cotton - Junji Su; Dandan Li; Wenmin Yuan; Ying Li; Jisheng Ju; Ning Wang; Pingjie Ling; Keyun Feng; Caixiang Wang (Theoretical and Applied Genetics, 2024)

The secondary visual cortex mediated the enhancement of associative learning on methamphetamine self-administration behaviors - Cai-ling Wang; Dan-ni Cao; Ning Wu; Ying-jie Zhu; Jin Li (Psychopharmacology, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Sustainable release of borate- and nitrate- electrolyte additives via metal-organic frameworks nanocapsules for stable lithium metal batteries - Jiaxing Yan; Jiaqi Li; Wenqiang Fang; Yuanhang Gao; Zuosu Qin; Mingwei Sun; Ying Zhang; Ning Zhang; Xiaohe Liu; Gen Chen (Chemical Engineering Journal, 2024)

Long-term subsoiling and tillage rotation increase carbon storage in soil aggregates and the abundance of autotrophs - Ying Shen; Renzheng Zhang; Qian Yang; Zhen Liu; Geng Li; Huifang Han; Yakov Kuzyakov; Tangyuan Ning (Applied Soil Ecology, 2024)

Retraction Note: China’s 2060 carbon-neutrality agenda: the nexus between energy consumption and environmental quality - Kaodui Li; Hongxin Ying; Yi Ning; Xiangmiao Wang; Mohammed Musah; Muntasir Murshed; Morrison Alfred; Yanhong Chu; Han Xu; Xinyi Yu; Xiaxin Ye; Qian Jiang; et al. (Environmental Science and Pollution Research, 2024)

Foliar uptake screening: A promising strategy for identifying wheat varieties with low lead accumulation - Liu-Xu Feng; Yu-Ning Li; Li-Ping Geng; Pei-Pei Gao; Xiang-Yu Li; Ding-Hao Li; Gui-Li Hua; Quan-Li Zhao; Wen-Ju Liu; Pei-Ying Xue (Science of The Total Environment, 2024)

Integration of seeding-induced crystallization with microbubble aeration for membrane fouling and wetting control in vacuum membrane distillation - Wei Zhang; Qian Xiao; Shuili Yu; Xingli Ji; Rongsheng Ning; Ying Xu; Pan Li (Desalination, 2024)

Infection by virulent wMelPop Wolbachia improves learning and memory capacity in Drosophila melanogaster - Meng-Yan Chen; Dong Li; Zhi-Ning Wang; Feng-Zhen Xu; Yi-Wei Feng; Qiong-Lin Yu; Ying-Ying Wang; Shu Zhang; Yu-Feng Wang (Animal Behaviour, 2024)

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

Polyvinyl alcohol-based multifunctional hydrogel film: A novel strategy for food preservation packaging - Wei Gong; Wan-ying He; Yi-yang Hou; Yu-xin Li; Yuan-yuan Hu; Bei-wei Zhu; Jiang-ning Hu (Food Bioscience, 2024)

Treatment of emerging pyrrolizidine alkaloids in drinking water by UV/persulfate process: Kinetics, energy efficiency and degradation pathway - Menghong Gao; Shuili Yu; Li'an Hou; Xingli Ji; Rongsheng Ning; Ying Xu; Lei Li (Chemical Engineering Journal, 2024)

Perovskite/organic tandem device to realize light detection and emission dual function - Ning Li; Xin Hu; Yu Tang; Yanlian Lei; Ying Suet Lau; Qian Chen; Xiubao Sui; Furong Zhu (Chemical Engineering Journal, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Molecular insights into the catabolism of dibutyl phthalate in Pseudomonas aeruginosa PS1 based on biochemical and multi-omics approaches - Huan Du; Ji-Liang Cheng; Zhi-Yong Li; Huai-Ning Zhong; Shuang Wei; Yu-Juan Gu; Can-Can Yao; Miaoyue Zhang; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Ferrocene-functionalized zirconium-oxo clusters for achieving high-performance thermocatalytic redox reactions - Su-Juan Yao; Jiao-Min Lin; Long-Zhang Dong; Ying-Lin Li; Ning Li; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Carbon doping enhances the fluoride removal performance of aluminum-based adsorbents - Lin Tong; Ying Miao; Shushu Li; Ning Bao; Qingwen Zhou; Yuhuan Yang; Changqing Ye (Environmental Science and Pollution Research, 2024)

Synthesis and Application of Specific N2H4 Fluorescent Probes with AIE Effect Based on Pyrazole Structure - Yun-Shang Yang; Zhen Zhang; Ying-Peng Zhang; Yu-Ning Liang; Xing-Xing Li; Zhi-Dong Teng (Journal of Fluorescence, 2024)

Characterization and removal mechanism of fluoroquinolone-bioremediation by fungus Cladosporium cladosporioides 11 isolated from aquacultural sediments - Ning Ma; Hongyu Zhang; Lilai Yuan; Yingren Li; Wenbo Yang; Ying Huang (Environmental Science and Pollution Research, 2024)

Photocatalysis uranium (VI) reduction at Cu2O/WO3|FTO Z-scheme heterojunction systems - Ning Liu; Hongsen Zhang; Jiahui Zhu; Qi Liu; Jing Yu; Rongrong Chen; Ying Li; Rumin Li; Jun Wang (Journal of Environmental Chemical Engineering, 2024)

Unveiling vertical ozone variation with UAV-Based monitoring and modeling: A new challenge for city-level ozone pollution control in the pearl river delta region - Haoxiang Xu; Ying Li; Changqing Lin; Zhi Ning; Chanfang Liu; Boru Mai; Xuejiao Deng; Shidong Fan; Jinlan Li (Atmospheric Environment, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Inhibition of TLR4/NF-κB pathway and endoplasmic reticulum stress by overexpressed S100A4 ameliorates retinal ischemia-reperfusion injury of mice - Jiayi Yang; Xiao Zhang; Ying Li; Ning Yang; Jinyuan Luo; Tao He; Yiqiao Xing (Molecular Neurobiology, 2024)

A novel safer CD19CAR with shRNA interference of IFN-γ can reduce multiple cytokine levels without significantly compromising its killing efficacy - Ping Zhang; Peiting Ying; Hongzhe Li; Ning Zhao; Rongrong Liu; Sisi Li; Weiqun Xu; Yang Tang; Yongmin Tang (Apoptosis, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Performance assessment of solar photovoltaic-based constructed wetland for sustainable rural wastewater treatment - Ye Yang; Chao-Kun Li; Liu Han; Zhi-Peng Yang; Ning-Ning Xiao; Nan Zhang; Ying-Ying Dong; Zhi-Wen Chen; Hui Xi; Wen-Dong Wang (Journal of Water Process Engineering, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

The kinetic study on key quality and microbial content of fresh-cutting Chinese yams (Dioscorea opposita Thunb.) at different storage temperatures - Zhiyao Li; Youqing Wen; Yueling Yan; Ying Ning; Maomei Xie; Yiting Zhu; Haixia Wang (Journal of Stored Products Research, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Occurrence of polyhalogenated carbazoles and the combined effects with heavy metals on variation in bacterial communities in estuarine sediments - Shanmin Hu; Minggang Zheng; Yingdi Mu; Aifeng Liu; Yuqing Jiang; Ying Li; Ke Ning; Ling Wang (Marine Pollution Bulletin, 2024)

DNA hypomethylation-associated transcriptional rewiring enables resistance to heavy metal mercury (Hg) stress in rice - Weixuan Cong; Ning Li; Yiling Miao; Yuxi Huang; Wenhao Zhao; Ying Kang; Bingqi Zhang; Jinbin Wang; Jiayu Zhang; Yinhe Lv; Jiamo Li; Jian Zhang; et al. (Journal of Hazardous Materials, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Detecting miRNA-21 using dual-mode biosensor via click chemistry-mediated variable temperature amplification reaction - Xiaofang Liu; Qun Wang; Ya Zhang; Zhihao Yang; Ning Li; Ying Xu; Mei Yang; Danqun Huo; Changjun Hou (Chemical Engineering Journal, 2024)

MiRNA320a Inhibitor-Loaded PLGA-PLL-PEG Nanoparticles Contribute to Bone Regeneration in Trauma-Induced Osteonecrosis Model of the Femoral Head - Ying Zhang; Chuan Li; Qiushi Wei; Qiang Yuan; Wei He; Ning Zhang; Yiping Dong; Zhenhao Jing; Leilei Zhang; Haibin Wang; Xiangyang Cao (Tissue Engineering and Regenerative Medicine, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Fe-MMT/WO3 composites for chemical and photocatalysis synergistic reduction of uranium (VI). - Ning Liu; Jing Yu; Hongsen Zhang; Jiahui Zhu; Qi Liu; Rongrong Chen; Ying Li; Rumin Li; Jun Wang (Chemosphere, 2023)

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

Compound hot and ozone extremes in urban China - Ning An; Yang Chen; Panmao Zhai; Jiandong Li; Ying Wei (Urban Climate, 2023)

Identifying the key factors affecting the trimethylamine N-oxide content of teleost fishes collected from the marginal seas of China and the epipelagic zone of the northwest Pacific Ocean - Qingjing Hu; Wanyu Zhao; Keming Qu; Ning An; Lingxiao Li; Yuqiu Wei; Ying Bai; Tao Jiang; Jufa Chen; Fangqun Dai; Hongsheng Wang; Zhengguo Cui (Science of The Total Environment, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Microbiome variability in invasive coral (Tubastraea aurea) in response to diverse environmental stressors - Gowri Krishna Girija; Li-Chun Tseng; Yu-Ling Chen; Pei-Jie Meng; Jiang-Shiou Hwang; Ying-Ning Ho (Frontiers in Marine Science, 2023)
The Indo-Pacific native azooxanthellate Tubastraea (Scleractinia) has been identified as an invasive marine species with substantial environmental, economic, and social implications worldwide. Despite their exceptional invasive capacity, our understanding of the role of their symbiotic microbiota in host resilience, as well as their response to ambient environmental conditions, remains limited. In this study, we analyzed the symbiotic bacterial communities found in the tissue and mucus of Tubastraea aurea from different habitats along the northeastern coast of Taiwan. These habitats included two extreme sites (a hydrothermal vent [HV] and a copper mining [CM] site) and two normal environments (inlet of a nuclear power plant [NPP] and a habitat adjacent to a conservation zone [CZ]). We employed full-length 16S rRNA sequencing (~1.5 kilobases) to determine coral-associated microbiome responses to local environments. Results showed significant variations in bacterial communities between corals from extreme and normal habitats. Chemoheterotrophic Endozoicomonas bacteria dominated the tissue samples from the HV and CM sites, whereas phototrophic Synechococcus cyanobacteria dominated the NPP and CZ sites. Hydrographic parameters such as pH, salinity, biological oxygen demand, turbidity, and concentration of heavy metals (e.g., Cu and Fe) increased at the HV and CM sites compared with those at the NPP and CZ sites. This difference created more stressful conditions at the HV and CM sites. The microbial assemblages associated with T. aurea exhibited a prevalence of diverse symbiotic bacteria that could potentially contribute to the host’s ability to adapt and survive in challenging ecological conditions. Therefore, these advantageous microorganisms, along with the host’s physiological mechanisms of dispersion, range expansion, and invasiveness, may enhance the resilience and ability of T. aurea to thrive in extreme environments.

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Corrigendum to “Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni” [J Hazard Mater 452 (2023) 131367] - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Microbial metabolic activity in metal(loid)s contaminated sites impacted by different non-ferrous metal activities - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Jianli Liu; Miaomaio Li; Bang Liu; Wancheng Pang; Ying Cao; Ruofei Li; Robert Duran (Journal of Hazardous Materials, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

New insights into triazole fungicide-caused hematopoietic abnormality in zebrafish based on GRα screening developmental toxicity - Yue Wang; Lingyu Ren; Ying Ren; Mengdan Chai; Xia Ning; Guangke Li; Nan Sang (Environmental Pollution, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Risk SNP in a transcript of RP11-638I2.4 increases lncRNA–YY1 interaction and pancreatic cancer susceptibility - Ming Zhang; Yanmin Li; Fuwei Zhang; Hui Geng; Yimin Cai; Zequn Lu; Bin Li; Caibo Ning; Wenzhuo Wang; Haijie Li; Jianbo Tian; Ying Zhu; et al. (Archives of Toxicology, 2023)

Biodegradation of additive-free polypropylene by bacterial consortia enriched from the ocean and from the gut of Tenebrio molitor larvae - Zhuo-Ning Xian; Chao-Fan Yin; Li Zheng; Ning-Yi Zhou; Ying Xu (Science of The Total Environment, 2023)

Temporal expansion of the nighttime light images of SDGSAT-1 satellite in illuminating ground object extraction by joint observation of NPP-VIIRS and sentinel-2A images - Bo Yu; Fang Chen; Cheng Ye; Ziwen Li; Ying Dong; Ning Wang; Lei Wang (Remote Sensing of Environment, 2023)

Treatment of high-salinity brine containing dissolved organic matters by vacuum membrane distillation: A fouling mitigation approach via microbubble aeration - Wei Zhang; Shuili Yu; Rongsheng Ning; Pan Li; Xingli Ji; Ying Xu (Journal of Environmental Management, 2023)

An ultrasensitive electrochemical sensor based on antimonene simultaneously detect multiple heavy metal ions in food samples - Ya Zhang; Ying Xu; Ning Li; Xiaofang Liu; Yi Ma; SiyiYang; Huibo Luo; Changjun Hou; Danqun Huo (Food Chemistry, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Tartary buckwheat-derived exosome-like nanovesicles against starch digestion and their interaction mechanism - Dan Li; Guifang Cao; Xiaolin Yao; Yongli Yang; Dan Yang; Ning Liu; Ying Yuan; Katsuyoshi Nishinari; Xi Yang (Food Hydrocolloids, 2023)

Investigation on the potential adverse outcome pathway of the sensitive endpoint for nephrotoxicity induced by gardenia yellow based on an integrated strategy using bioinformatics analysis and in vitro testing validation - Jiang Liang; Hong-Xin Wei; Ying-Ying Zhou; Li-Li Hao; Jun-Yu Ning; Lei Zhang (Food and Chemical Toxicology, 2023)

Boosting photocatalysis of hydrazone-linked covalent organic frameworks through introducing electron-rich conjugated aldehyde - Qingqing Tang; Ying-Ying Gu; Jing Ning; Yingkui Yan; Li Shi; Mengshi Zhou; Hongtao Wei; Xiaohui Ren; Xuehui Li; Junxia Wang; Chao Tang; Long Hao; et al. (Chemical Engineering Journal, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Unexpected association between ambient ozone and adult insomnia outpatient visits: A large-scale hospital-based study - Dawei Li; Lili Yang; Nan Wang; Yuegu Hu; Yumeng Zhou; Ning Du; Na Li; Xiaoling Liu; Chunyan Yao; Na Wu; Ying Xiang; Yafei Li; et al. (Chemosphere, 2023)

Multiscale model to resolve the chemical environment in a pressurized CO2-captured solution electrolyzer - Ning Liu; Longfei Chen; Kai Deng; Hao Feng; Ying Zhang; Jingjing Duan; Dong Liu; Qiang Li (Science Bulletin, 2023)

Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Cereal polyphenols inhibition mechanisms on advanced glycation end products and regulation on type 2 diabetes - Lezhen Dong; Ying Li; Qin Chen; Yahui Liu; Zufang Wu; Daodong Pan; Ning Yan; Lianliang Liu (Critical Reviews in Food Science and Nutrition, 2023)

Occurrence and risk levels of antibiotic pollution in the coastal waters of eastern China - Ning Xu; Yi Shen; Lei Jiang; Bin Jiang; Ying Li; Qingbin Yuan; Yunhai Zhang (Environmental Science and Pollution Research, 2023)

Effect of different doses of trichloroisocyanuric acid on aquaculture pond water - Hong-yu Zhang; Ying Huang; Ning Ma; Hai-bo Wang; Xiao-yong Zhang; Ying-chun Xing; Lei Xia; Guang Yang; Li-lai Yuan; Ying-ren Li (Aquaculture, 2023)

Phase-change material cooling blanket: A feasible cooling choice during transport after exercise-induced hyperthermia - Xin Wang; Xueyi Shang; Xin Li; Shuyuan Liu; Bin Lai; Lizhi Ma; Ying Sun; Lan Ma; Bo Ning; Yan Li; Qian Wang (Journal of Thermal Biology, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Animal experiments on respiratory viruses and analogous studies of infection factors for interpersonal transmission - Yuxuan Liao; Shurui Guo; Ning Mao; Ying Li; Jin Li; Enshen Long (Environmental Science and Pollution Research, 2023)

Temperature-dependent mycotoxins production investigation in Alternaria infected cherry by ultra-high performance liquid chromatography and Orbitrap high resolution mass spectrometry - Yanshen Li; Ying Shao; Ya'ning Zhu; Anqi Chen; Jingyao Qu; Yonglin Gao; Sunan Lu; Pengjie Luo; Xin Mao (International Journal of Food Microbiology, 2023)

Influences of high hydrostatic pressure on structures and properties of mung bean starch and quality of cationic starch - Ning Wang; Ying Dong; Yangyong Dai; Hong Zhang; Hanxue Hou; Wentao Wang; Xiuzhen Ding; Hui Zhang; Cheng Li (Food Research International, 2023)

Novel flavan-3-ol-dithiothreitol conjugates derived from the degradation of grape seed proanthocyanidins and their neuroprotective potential - Meng Huang; Meng Li; Ying Zhang; Huan Gong; Yuju Zhou; Danping Zhu; Lingxi Li; Ning Ma; Yan Cui (Food Chemistry, 2023)

Thin-layer chromatography coupled with HPLC-DAD/UHPLC-HRMS for target and non-target determination of emerging halogenated organic contaminants in animal-derived foods - Ying Li; Ling Wang; Minggang Zheng; Yongfeng Lin; Hongyan Xu; Aifeng Liu; Yi Hua; Yuqing Jiang; Ke Ning; Shanmin Hu (Food Chemistry, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Environmental exposure to triazole fungicide causes left-right asymmetry defects and contributes to abnormal heart development in zebrafish embryos by activating PPARγ-coupled Wnt/β-catenin signaling pathway - Yue Wang; Ying Ren; Xia Ning; Guangke Li; Nan Sang (Science of The Total Environment, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Early Cretaceous palynofloras from the Bongor basin, Chad, and their palaeoenvironmental and palaeoclimatic significances - Ying Hu; Jie Hu; Yebo Du; Huinan Lu; Ning Yang; Li Wang; Hong-He Xu (Journal of African Earth Sciences, 2023)

Hydrodeoxygenation of lignin-derived phenolic compounds over Ru/TiO2 catalyst: Effect of TiO2 morphology - Zhuojie Zhong; Junxuan Li; Minyin Jian; Riyang Shu; Zhipeng Tian; Chao Wang; Ying Chen; Ning Shi; Yanxue Wu (Fuel, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Rearranged oleananes in Tertiary oils from the Baiyun Sag, Pearl River Mouth Basin, South China Sea: identification, distribution and geochemical significance - Xiaolin Lu; Meijun Li; Youchuan Li; Yongcai Yang; Ning Wang; Zichao Ran; Ying Fu; Sajjad Ali (Organic Geochemistry, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

A molecular-level coupling model of fluid catalytic cracking and hydrotreating processes to improve gasoline quality - Xinglong Qin; Lei Ye; Jichang Liu; Youhao Xu; Alqubati Murad; Qiang Ying; Haitao Shen; Xin Wang; Lixin Hou; Xin Pu; Xin Han; Jiangbing Li; et al. (Chemical Engineering Journal, 2023)

Anionic metal-organic framework modified separator boosting efficient Li-ion transport - Jiaqi Li; Long Chen; Fengling Wang; Zuoyu Qin; Ying Zhang; Ning Zhang; Xiaohe Liu; Gen Chen (Chemical Engineering Journal, 2023)

How do temperature, humidity, and air saturation state affect the COVID-19 transmission risk? - Ning Mao; Dingkun Zhang; Yupei Li; Ying Li; Jin Li; Li Zhao; Qingqin Wang; Zhu Cheng; Yin Zhang; Enshen Long (Environmental Science and Pollution Research, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Wide distribution of the sad gene cluster for sub‐terminal oxidation in alkane utilizers - Chao‐Fan Yin; Ying Xu; Tao Li; Ning‐Yi Zhou (Environmental Microbiology, 2022)
Alkane constitutes major fractions of crude oils, and its microbial aerobic degradation dominantly follows the terminal oxidation and the sub‐terminal pathways. However, the latter one received much less attention, especially since the related genes were yet to be fully defined. Here, we isolated a bacterium designated Acinetobacter sp. strain NyZ410, capable of growing on alkanes with a range of chain lengths and derived sub‐terminal oxidation products. From its genome, a s econdary a lcohol d egradation gene cluster ( sad ) was identified to be likely involved in converting the aliphatic secondary alcohols (the sub‐terminal oxidation products of alkanes) to the corresponding primary alcohols by removing two‐carbon unit. On this cluster, sadC encoded an alcohol dehydrogenase converting the aliphatic secondary alcohols to the corresponding ketones; sadD encoded a Baeyer–Villiger monooxygenase catalysing the conversion of the aliphatic ketones to the corresponding esters; SadA and SadB are two esterases hydrolyzing aliphatic esters to the primary alcohols and acetic acids. Bioinformatics analyses indicated that the sad cluster was widely distributed in the genomes of probable alkane degraders, apparently coexisting (64%) with the signature enzymes AlkM and AlmA for alkane terminal oxidation in 350 bacterial genomes. It suggests that the alkane sub‐terminal oxidation may be more ubiquitous than previously thought.

Mitigation of atrazine-induced oxidative stress on soybean seedlings after co-inoculation with atrazine-degrading bacterium Arthrobacter sp. DNS10 and inorganic phosphorus-solubilizing bacterium Enterobacter sp. P1 - Zhao Jiang; Qi Shao; Yuxin Chu; Ning An; Bo Cao; Zheyi Ren; Jin Li; Jianhua Qu; Maofeng Dong; Ying Zhang (Environmental Science and Pollution Research, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

In sharing and explaining the history of socio-ecological practice, we must act as intergenerational mediators between the past and present historymakers - Yuncai Wang; Hui Wang; Wentao Yan; Wei Gao; Chundi Chen; Ying Chen; Wei-Ning Xiang; Yiman Li (Socio-Ecological Practice Research, 2022)

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Dihydroartemisinin beneficially regulates splenic immune cell heterogeneity through the SOD3-JNK-AP-1 axis - Yiwei Zhang; Qilong Li; Ning Jiang; Ziwei Su; Quan Yuan; Lei Lv; Xiaoyu Sang; Ran Chen; Ying Feng; Qijun Chen (Science China Life Sciences, 2022)

Two-stage cultivation of Scenedesmus acuminatus with nitrogen and sulfur for growth and lipid accumulation - Ying Zhang; Hongxiao Shen; Ping Zhong; Zhenzhu Huang; Ning Xu; Aifen Li (Journal of Applied Phycology, 2022)

RETRACTED ARTICLE: China’s 2060 carbon-neutrality agenda: the nexus between energy consumption and environmental quality - Kaodui Li; Hongxin Ying; Yi Ning; Xiangmiao Wang; Mohammed Musah; Muntasir Murshed; Morrison Alfred; Yanhong Chu; Han Xu; Xinyi Yu; Xiaxin Ye; Qian Jiang; et al. (Environmental Science and Pollution Research, 2022)

Effects of U on the growth, reactive oxygen metabolism and osmotic regulation in radish (Raphanus sativus L.) - Guo Wu; Xi Chen; Ting Zheng; Pi-xian Xiao; Ning-ying Zhong; Xiu-lin Yang; Yi Li; Wei Li (Environmental Science and Pollution Research, 2022)

Genome-wide locus-specific DNA methylation repatterning may facilitate rapid evolution of mercury resistance in rice - Weixuan Cong; Ning Li; Jinbin Wang; Ying Kang; Yiling Miao; Chunming Xu; Ziqi Wang; Tongtong Liu; Lei Gong; Bao Liu; Xiufang Ou (Genes & Genomics, 2022)

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

Enhanced photosynthetic nitrogen use efficiency and increased nitrogen allocation to photosynthetic machinery under cotton domestication - Zhang-Ying Lei; Heng Wang; Ian J. Wright; Xin-Guang Zhu; Ülo Niinemets; Zi-Liang Li; Dong-Sheng Sun; Ning Dong; Wang-Feng Zhang; Zhong-Li Zhou; Fang Liu; Ya-Li Zhang (Photosynthesis Research, 2021)

Paraburkholderia sp. GD17 improves rice seedling tolerance to salinity - Ruanming Zhu; Yuting Cao; Guangzhe Li; Ying Guo; Lianju Ma; Ning Bu; Lin Hao (Plant and Soil, 2021)

A new benzophenone with biological activities from metabolites of butyrolactone I in rat faeces - Bing Liu; Ning Chen; Ying Xu; Jia-Wei Zhang; Yuan Sun; Li-Zhu Zhao; Yu-bin Ji (Natural Product Research, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Sublethal dose of warfarin induction promotes the accumulation of warfarin resistance in susceptible Norway rats - Xiaohui Ma; Yan Chen; Yaqi Ying; Yuanzhao Geng; Dawei Wang; Ning Li; Xiao-Hui Liu; Ying Song (Journal of Pest Science, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Integrated LSM-DFN Modeling of Naturally Fractured Reservoirs: Roughness Effect on Elastic Characteristics - Ning Liu; Yang-Ying Li; Li-Yun Fu; Yue Kong; Wu-Shuang Li (Pure and Applied Geophysics, 2021)

Editorial Expression of Concern: The bio-mitigation of acetochlor in soil using Rhodopseudomonas capsulata in effluent after wastewater treatment - Pan Wu; Bo Cao; Ying Zhang; Wenbin Li; Yanling Wang; Yuan Wu; Ning Li (Journal of Soils and Sediments, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Genetic diversity analysis of Topmouth Culter (Culter alburnus) based on microsatellites and D-loop sequences - Ning Sun; Dong-Mei Zhu; Qing Li; Gui-Ying Wang; Jian Chen; Feifei Zheng; Pei Li; Yan-Hong Sun (Environmental Biology of Fishes, 2021)

Mycorrhiza-induced plant defence responses in trifoliate orange infected by Phytophthora parasitica - Li Tian; Ying-Ning Zou; Qiang-Sheng Wu; Kamil Kuča (Acta Physiologiae Plantarum, 2021)

Effects of sulfur limitation on nitrogen and sulfur uptake and lipid accumulation in Scenedesmus acuminatus - Qianya Wang; Ying Zhang; Huijuan Wu; Ning Xu; Aifen Li (Journal of Applied Phycology, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Correction to: The H741D mutation in Tac1p contributes to the upregulation of CDR1 and CDR2 expression in Candida albicans - Jin-Yan Liu; Bing Wei; Ying Wang; Ce Shi; Wen-Jing Li; Yue Zhao; Ling-Ning Meng; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2020)

The H741D mutation in Tac1p contributes to the upregulation of CDR1 and CDR2 expression in Candida albicans - Jin-Yan Liu; Bing Wei; Ying Wang; Ce Shi; Wen-Jing Li; Yue Zhao; Ling-Ning Meng; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2020)

LncRNA A2M-AS1 lessens the injury of cardiomyocytes caused by hypoxia and reoxygenation via regulating IL1R2 - Xue-Lian Song; Fei-Fei Zhang; Wen-Jing Wang; Xin-Ning Li; Yi Dang; Ying-Xiao Li; Qian Yang; Mei-Jing Shi; Xiao-Yong Qi (Genes & Genomics, 2020)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Secreted frizzled-related protein 2 prevents pressure-overload-induced cardiac hypertrophy by targeting the Wnt/β-catenin pathway - Wen-Ying Wei; Qing Zhao; Wen-zhong Zhang; Mao-jing Wang; Yan Li; Shi-zhong Wang; Ning Zhang (Molecular and Cellular Biochemistry, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Methionine Sulfoxide Reductases Are Related to Arsenic Trioxide-Induced Oxidative Stress in Mouse Liver - Gaolong Zhong; Fang Wan; Hao Yan; Zhijun Ning; Congcong Wang; Ying Li; Jiaqiang Pan; Zhaoxin Tang; Zengming Yang; Riming Huang; Lianmei Hu (Biological Trace Element Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Augmentation of danusertib’s anticancer activity against melanoma by blockage of autophagy - Yuan-Yuan Shang; Nan Yu; Li Xia; Ying-Yao Yu; Chun-mei Ma; Ya-Ning Jiao; Yun-feng Li; Yuan Wang; Jie Dang; Weichao Li (Drug Delivery and Translational Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Evidences of aromatic degradation dominantly via the phenylacetic acid pathway in marine benthic Thermoprofundales - Wei‐Wei Liu; Jie Pan; Xiaoyuan Feng; Meng Li; Ying Xu; Fengping Wang; Ning‐Yi Zhou (Environmental Microbiology, 2020)
Summary Thermoprofundales (Marine Benthic Group D archaea, MBG‐D) is a newly proposed archaeal order and widely distributed in global marine sediment, and the members in the order may play a vital role in carbon cycling. However, the lack of pure cultures of these oeganisms has hampered the recognition of their catabolic roles. Here, by constructing high‐quality metagenome‐assembled genomes (MAGs) of two new subgroups of Thermoprofundales from hydrothermal sediment and predicting their catabolic pathways, we here provide genomic evidences that Thermoprofundales are capable of degrading aromatics via the phenylacetic acid (PAA) pathway. Then, the gene sequences of phenylacetyl‐CoA ligase (PCL), a key enzyme for the PAA pathway, were searched in reference genomes. The widespread distribution of PCL genes among 14.9% of archaea and 75.9% of Thermoprofundales further supports the importance of the PAA pathway in archaea, particularly in Thermoprofundales where no ring‐cleavage dioxygenases were found. Two PCLs from Thermoprofundales MAGs, PCL M8‐3 and PCL M10‐15 , were able to convert PAA to phenylacetyl‐CoA (PA‐CoA) in vitro , demonstrating the involvement of Thermoprofundales in aromatics degradation through PAA via CoA activation. Their acid tolerance (pH 5–7), high‐optimum temperatures (60°C and 80°C), thermostability (stable at 60°C and 50°C for 48 h) and broad substrate spectra imply that Thermoprofundales are capable of transforming aromatics under extreme conditions. Together with the evidence of in situ transcriptional activities for most genes related to the aromatics pathway in Thermoprofundales, these genomic, and biochemical evidences highlight the essential role of this ubiquitous and abundant archaeal order in the carbon cycle of marine sediments.

Chachezhania antarctica gen. nov., sp. nov., a novel member of the family ‘Rhodobacteraceae’ isolated from Antarctic seawater - Xiao-xue Yuan; Ning Wang; Meng-yao Zhang; Xiu-lan Chen; Chun-yang Li; Yu-zhong Zhang; Mei Shi; Xi-ying Zhang (Antonie van Leeuwenhoek, 2019)

Functional characterization of three MATE genes in relation to aluminum-induced citrate efflux from soybean root - Ying Zhou; Zhengbiao Wang; Li Gong; Anle Chen; Ning Liu; Sha Li; Haoran Sun; Zhenming Yang; Jiangfeng You (Plant and Soil, 2019)

iTRAQ-based analysis of 17β-estradiol induced proteome in Chinese tongue sole Cynoglossus semilaevis - Ying Zhu; Yangzhen Li; Hailong Li; Lei Wang; Ning Zhang; Yang Liu; Liang Meng; Xiwen Xu; Zhongdian Dong; Min Wei; Hua Guo; Zhongkai Cui; et al. (Journal of Oceanology and Limnology, 2019)

Dynamic expressions of hypothalamic genes regulate seasonal breeding in a natural rodent population - Dawei Wang; Ning Li; Lin Tian; Fei Ren; Zhengguang Li; Yan Chen; Lan Liu; Xiangfa Hu; Xuechang Zhang; Ying Song; Roelof A. Hut; Xiao‐Hui Liu (Molecular Ecology, 2019)
Seasonal breeding is a universal reproductive strategy in many animals. Hypothalamic genes, especially type 2 and 3 iodothyronine deiodinases ( Dio2 / 3 ), RFamide‐related peptide 3 ( Rfrp‐3 ), kisspeptin ( Kiss‐1 ) and gonadotropin‐releasing hormone ( GnRH ), are involved in a photoperiodic pathway that encodes seasonal signals from day length in many vertebrate species. However, the seasonal expression patterns of these genes in wild mammals are less studied. Here, we present a four‐year field investigation to reveal seasonal rhythm and age‐dependent reproductive activity in male Brandt's voles ( Lasiopodomys brandtii ) and to detect relationships among seasonal expression profiles of hypothalamic genes, testicular activity, age and annual day length. From breeding season (April) to nonbreeding season (October), adult male voles displayed a synchronous peak in gonadal activity with annual day length around summer solstice, which was jointly caused by age structure shifts and age‐dependent gonadal development patterns. Overwintered males maintained reproductive activity until late in the breeding season, whereas most newborn males terminated gonadal development completely, except for a minority of males born early in spring. Consistently, the synchronous and opposite expression profiles of Dio2/3 suggest their central function to decode photoperiodic signals and to predict the onset of the nonbreeding season. Moreover, changes in Dio2/3 signals may guide the actions of Kiss‐1 and Rfrp‐3 to regulate the age‐dependent divergence of reproductive strategy in wild Brandt's vole. Our results provide evidence on how hypothalamic photoperiod genes regulate seasonal breeding in a natural rodent population.

The bio-mitigation of acetochlor in soil using Rhodopseudomonas capsulata in effluent after wastewater treatment - Pan Wu; Bo Cao; Ying Zhang; Wenbin Li; Yanling Wang; Yuan Wu; Ning Li (Journal of Soils and Sediments, 2019)

iTRAQ-based proteomic analysis of resistant Nicotiana tabacum in response to Bemisia tabaci infestation - Song-tao Zhang; Yue Long; Song-jie Zhang; Ning Li; De-xin Chen; Hong-fang Jia; Hong-ying Zhang; Yong-xia Yang (Arthropod-Plant Interactions, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

Altered Expression of Zinc Transporter ZIP12 in Broilers of Ascites Syndrome Induced by Intravenous Cellulose Microparticle Injection - Hao Cui; Jianxin Liu; Guming Xu; Xujiao Ren; Zhenbiao Li; Ying Li; Zhangyong Ning (Biochemical Genetics, 2019)

Changes in mortality and economic vulnerability to climatic hazards under economic development at the provincial level in China - Jidong Wu; Ying Li; Tao Ye; Ning Li (Regional Environmental Change, 2019)

Application of a Simple Quantitative Assessment of Atherosclerotic Lesions in Freshly Isolated Aortas from Rabbits - Li-Jun Zhao; Ying Xiao; Xia Meng; Ning Wang; Y. James Kang (Cardiovascular Toxicology, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

The complete chloroplast genome of Paeonia rockii (Paeoniaceae), an endangered endemic species to China - Guoqing Bai; Hewei Guo; Ning Zhao; Sifeng Li; Ying Zhang (Conservation Genetics Resources, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

miR-4326 promotes lung cancer cell proliferation through targeting tumor suppressor APC2 - Guopeng Xu; Zhongwei Zhang; Li Zhang; Ying Chen; Ning Li; Yantian Lv; Yong Li; Xiao Xu (Molecular and Cellular Biochemistry, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

RNA-seq analysis provides insight into reprogramming of culm development in Zizania latifolia induced by Ustilago esculenta - Zhi-Dan Wang; Ning Yan; Zheng-Hong Wang; Xiao-Huan Zhang; Jing-Ze Zhang; Hui-Min Xue; Li-Xia Wang; Qi Zhan; Ying-Ping Xu; De-Ping Guo (Plant Molecular Biology, 2017)

Two distinct cinnamoyl-CoA reductases in Selaginella moellendorffii offer insight into the divergence of CCRs in plants - Nan Chao; Shuang Li; Ning Li; Qi Qi; Wen-Ting Jiang; Xiang-Ning Jiang; Ying Gai (Planta, 2017)

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli - Heng Li; Xiao-fei Shen; Xin-e Zhou; Yan-e Shi; Lu-xia Deng; Yi Ma; Xiao-ying Wang; Jing-yu Li; Ning Huang (Journal of Zhejiang University-SCIENCE B, 2017)

Characterization of the cinnamoyl-CoA reductase (CCR) gene family in Populus tomentosa reveals the enzymatic active sites and evolution of CCR - Nan Chao; Ning Li; Qi Qi; Shuang Li; Tong Lv; Xiang-Ning Jiang; Ying Gai (Planta, 2017)

Inhibitory effect of Shenqi Fuzheng injection combined with docetaxel on lung cancer cells - Bo-yu Dong; Cheng Wang; Li Tan; Ning Tan; Meng-di Zhao; Yang Lu; Shou-ying Du (Journal of Zhejiang University-SCIENCE B, 2017)

Androgenesis, gynogenesis, and parthenogenesis haploids in cucurbit species - Yan-Qi Dong; Wei-Xing Zhao; Xiao-Hui Li; Xi-Cun Liu; Ning-Ning Gao; Jin-Hua Huang; Wen-Ying Wang; Xiao-Li Xu; Zhen-Hai Tang (Plant Cell Reports, 2016)

Quantitative Proteome Profiling of Street Rabies Virus-Infected Mouse Hippocampal Synaptosomes - Xiaoning Sun; Ning Shi; Ying Li; Chunyan Dong; Maolin Zhang; Zhenhong Guan; Ming Duan (Current Microbiology, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Erratum to: The Clinical Utility of TIMP3 Expression in ACTH-Secreting Pituitary Tumor - Bowen Sun; Xiaohai Liu; Yakun Yang; Congxin Dai; Ying Li; Yonghui Jiao; Zhenqing Wei; Yong Yao; Ming Feng; Xinjie Bao; Kan Deng; Ning Wang; et al. (Journal of Molecular Neuroscience, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

The Clinical Utility of TIMP3 Expression in ACTH-Secreting Pituitary Tumor - Bowen Sun; Xiaohai Liu; Yakun Yang; Congxin Dai; Ying Li; Yonghui Jiao; Zhenqing Wei; Yong Yao; Ming Feng; Xinjie Bao; Kan Deng; Ning Wang; et al. (Journal of Molecular Neuroscience, 2016)

Combined effect between two functional polymorphisms of SLC6A12 gene is associated with temporal lobe epilepsy - JINGYUN LI; HUA LIN; FENGHE NIU; XILIN ZHU; NING SHEN; XIN WANG; LIPING LI; AIHUA LIU; XIAOPAN WU; WEI SUN; YUPING WANG; YING LIU (Journal of Genetics, 2015)

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression - Ying Wu; Tingting Jiang; Yue Sun; Zeyang Wang; Guizhen Guo; Shuai Sun; Jie Wang; Ning Li; Zhenhui Wang; Di Zhang; Yan Bai; Yang Gao; et al. (Plant Molecular Biology Reporter, 2015)

Age, petrogenesis and tectonic significance of the ferrobasalts in the Chagangnuoer iron deposit, western Tianshan - Ning-Bo Li; He-Cai Niu; Xing-Chun Zhang; Qiao-Song Zeng; Qiang Shan; Cong-Ying Li; Shuang Yan; Wu-Bin Yang (International Geology Review, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

Autophagy regulates insulin resistance following endoplasmic reticulum stress in diabetes - Ning Zhang; Ming-ming Cao; Han Liu; Guang-ying Xie; Yan-bo Li (Journal of Physiology and Biochemistry, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Patulin biodegradation by marine yeast Kodameae ohmeri - Xiaoyan Dong; Wei Jiang; Chunsheng Li; Ning Ma; Ying Xu; Xianghong Meng (Food Additives & Contaminants: Part A, 2015)

The association between the APE1 Asp148Glu polymorphism and prostate cancer susceptibility: a meta-analysis based on case–control studies - Xue Zhou; Li Wei; Guangjun Jiao; Wei Gao; Mingzhen Ying; Ning Wang; Yajie Wang; Chuan Liu (Molecular Genetics and Genomics, 2015)

Arbuscular mycorrhiza mediates glomalin-related soil protein production and soil enzyme activities in the rhizosphere of trifoliate orange grown under different P levels - Qiang-Sheng Wu; Yan Li; Ying-Ning Zou; Xin-Hua He (Mycorrhiza, 2015)

Halomonas shantousis sp. nov., a novel biogenic amines degrading bacterium isolated from Chinese fermented fish sauce - Wei Jiang; Chunsheng Li; Binghong Xu; Xiaoyan Dong; Ning Ma; Jinzhi Yu; Dongfeng Wang; Ying Xu (Antonie van Leeuwenhoek, 2014)

Molecular cloning and functional analysis of nine cinnamyl alcohol dehydrogenase family members in Populus tomentosa - Nan Chao; Shu-Xin Liu; Bing-Mei Liu; Ning Li; Xiang-Ning Jiang; Ying Gai (Planta, 2014)

Identification of a novel mitogen-activated protein kinase kinase gene (MKK2) in the oilseed rape Brassica campestris - Teng Guo Zhang; Yuan Yuan Wang; Juan Wang; Xiao Hui Xia; Ning Yang; Ying Li Yang; Wan Cang Sun (Biologia, 2014)

Hsa-miR-1246, hsa-miR-320a and hsa-miR-196b-5p inhibitors can reduce the cytotoxicity of Ebola virus glycoprotein in vitro - MiaoMiao Sheng; Ying Zhong; Yang Chen; JianChao Du; XiangWu Ju; Chen Zhao; GuiGen Zhang; LiFang Zhang; KangTai Liu; Ning Yang; Peng Xie; DangSheng Li; et al. (Science China Life Sciences, 2014)

5-HT2A receptor-mediated excitation on cerebellar fastigial nucleus neurons and promotion of motor behaviors in rats - Chang-Zheng Zhang; Qian-Xing Zhuang; Ye-Cheng He; Guang-Ying Li; Jing-Ning Zhu; Jian-Jun Wang (Pflügers Archiv - European Journal of Physiology, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Molecular cloning and characterization of the mitogen-activated protein kinase kinase gene (MKK4) and its promoter sequence from oilseed rape (Brassica campestris L.) - Teng Guo Zhang; Qiong Qiong Chen; Ning Wang; Xiao Hui Xia; Juan Wang; Yan Chang; Ying Li Yang; Ning Yang; Wan Cang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Urinary Concentrations of Parabens in Chinese Young Adults: Implications for Human Exposure - Wan-Li Ma; Lei Wang; Ying Guo; Li-Yan Liu; Hong Qi; Ning-Zheng Zhu; Chong-Jing Gao; Yi-Fan Li; Kurunthachalam Kannan (Archives of Environmental Contamination and Toxicology, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

SOD1 gene transfer into paraventricular nucleus attenuates hypertension and sympathetic activity in spontaneously hypertensive rats - Ning Yuan; Feng Zhang; Ling-Li Zhang; Juan Gao; Ye-Bo Zhou; Ying Han; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Fraction characteristics of rare earth elements in the surface sediment of Bohai Bay, North China - Yayan Xu; Jinming Song; Liqin Duan; Xuegang Li; Huamao Yuan; Ning Li; Peng Zhang; Ying Zhang; Sisi Xu; Mo Zhang; Xiaodan Wu; Xuebo Yin (Environmental Monitoring and Assessment, 2012)

Cross-linked enzyme aggregates of β-glucosidase from Prunus domestica seeds - Lei Chen; Ying-Dan Hu; Ning Li; Min-Hua Zong (Biotechnology Letters, 2012)

An initial screening for HIV-associated neurocognitive disorders of HIV-1 infected patients in China - Yulin Zhang; Luxin Qiao; Wei Ding; Feili Wei; Qingxia Zhao; Xicheng Wang; Ying Shi; Ning Li; Davey Smith; Dexi Chen (Journal of NeuroVirology, 2012)

Igf2-derived intronic miR-483 promotes mouse hepatocellular carcinoma cell proliferation - Ning Ma; Fuyuan Li; Dan Li; Yang Hui; Xidi Wang; Yu Qiao; Yanfen Zhang; Ying Xiang; Jianying Zhou; Lingyun Zhou; Xiaofei Zheng; Xu Gao (Molecular and Cellular Biochemistry, 2012)

The effect of down regulation of calcineurin Aα by lentiviral vector-mediated RNAi on the biological behavior of small-cell lung cancer and its bone metastasis - Ning-Qiang Ma; Li-Li Liu; Jie Min; Jun-Wei Wang; Wei-Feng Jiang; Yan Liu; Yan-Guo Feng; Hai-Chuan Su; Ying-Ming Feng; He-Long Zhang (Clinical & Experimental Metastasis, 2011)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

A rapid detection method for apoptosis and necrosis measurement using the Cellometer imaging cytometry - Leo Li-Ying Chan; Ning Lai; Elena Wang; Tim Smith; Xifeng Yang; Bo Lin (Apoptosis, 2011)

Characterization of the MHC class II α-chain gene in ducks - Liming Ren; Zhi Yang; Tao Wang; Yi Sun; Ying Guo; Ziding Zhang; Jing Fei; Yonghua Bao; Tong Qin; Jing Wang; Yinhua Huang; Xiaoxiang Hu; et al. (Immunogenetics, 2011)

Fine mapping and analyses of R SC8 resistance candidate genes to soybean mosaic virus in soybean - Dagang Wang; Ying Ma; Yongqing Yang; Ning Liu; Chunyan Li; Yingpei Song; Haijian Zhi (Theoretical and Applied Genetics, 2011)

Whole genome amplification in preimplantation genetic diagnosis - Ying-ming Zheng; Ning Wang; Lei Li; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Characterization of a novel wheat NAC transcription factor gene involved in defense response against stripe rust pathogen infection and abiotic stresses - Ning Xia; Gang Zhang; Xin-Ying Liu; Lin Deng; Gao-Lei Cai; Yi Zhang; Xiao-Jie Wang; Jie Zhao; Li-Li Huang; Zhen-Sheng Kang (Molecular Biology Reports, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Angiotensin-(1–7) and angiotension II in the rostral ventrolateral medulla modulate the cardiac sympathetic afferent reflex and sympathetic activity in rats - Li-Min Zhou; Zhen Shi; Juan Gao; Ying Han; Ning Yuan; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Association between transforming growth factor β1 polymorphisms and left ventricle hypertrophy in essential hypertensive subjects - Hai-Ying Xu; Xu-Wei Hou; Li-Fang Wang; Ning-Fu Wang; Jian Xu (Molecular and Cellular Biochemistry, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Reversal of coenzyme specificity and improvement of catalytic efficiency of Pichia stipitis xylose reductase by rational site-directed mutagenesis - Qi-Kai Zeng; Hong-Li Du; Jing-Fang Wang; Dong-Qing Wei; Xiao-Ning Wang; Yi-Xue Li; Ying Lin (Biotechnology Letters, 2009)

Minocycline attenuates cognitive impairment and restrains oxidative stress in the hippocampus of rats with chronic cerebral hypoperfusion - Zhi-You Cai; Yong Yan; Shan-Quan Sun; Jun Zhang; Liang-Guo HUANG; Ning Yan; Fang Wu; Jie-Ying Li (Neuroscience Bulletin, 2008)

Self-organized Polymer Aggregates with a Biomimetic Hierarchical Structure and its Superhydrophobic Effect - Ning Zhao; Xiao-Yan Zhang; Yan-Fang Li; Xiao-Ying Lu; Si-Lu Sheng; Xiao-Li Zhang; Jian Xu (Cell Biochemistry and Biophysics, 2007)

Successful tubes treatment of esophageal fistula - Ning Zhou; Wei-xing Chen; You-ming Li; Zhun Xiang; Ping Gao; Ying Fang (Journal of Zhejiang University-SCIENCE B, 2007)

Localization of putative stem cells and four cell populations with different differentiation degree in mouse mammary anlagen - Jianyong Han; Suying Cao; Hong Jin; Ying Liu; Meili Wang; Jiazhe Song; Ning Li (Histochemistry and Cell Biology, 2006)

Mammalian Pol III Promoter H1 can Transcribe shRNA Inducing RNAi in Chicken Cells - Jing Yuan; Xiaobo Wang; Ying Zhang; Xiaoxiang Hu; Jing Fei; Ning Li (Molecular Biology Reports, 2006)

shRNA Transcribed by RNA Pol II Promoter Induce RNA Interference in Mammalian Cell - Jing Yuan; Xiaobo Wang; Ying Zhang; Xiaoxiang Hu; Xuemei Deng; Jing Fei; Ning Li (Molecular Biology Reports, 2006)

Investigation of iodine concentration in salt, water and soil along the coast of Zhejiang, China - Ying-li Lu; Ning-jian Wang; Lan Zhu; Guo-xing Wang; Hui Wu; Lin Kuang; Wen-ming Zhu (Journal of Zhejiang University-SCIENCE B, 2005)